Matematyka

Autorzy:Joanna Czarnowska, Jolanta Wesołowska, Wojciech Babiański, Lech Chańko

Wydawnictwo:Nowa Era

Rok wydania:2014

Przeczytaj podany w ramce przykład 4.4 gwiazdek na podstawie 5 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

`a)\ sqrt(3+2sqrt2)=sqrt(3+2*1*sqrt2)=sqrt(1+2+2*1*sqrt2)=sqrt(1^2+2*1*sqrt2+sqrt2^2)=sqrt((1+sqrt2)^2)=1+sqrt2`  

 

`b)\ sqrt(27+10sqrt2)=sqrt(27+2*5*sqrt2)=sqrt(25+2+2*5*sqrt2)=sqrt(5^2+2*5*sqrt2+sqrt2^2)=sqrt((5+sqrt2)^2)=5+sqrt2`  

 

`c)\ sqrt(39+12sqrt3)=sqrt(39+2*6*sqrt3)=sqrt(36+3+2*6*sqrt3)=sqrt(6^2+2*6*sqrt3+sqrt3^2)=sqrt((6+sqrt3)^2)=6+sqrt3` 

 

`d)\ sqrt(21+4sqrt5)=sqrt(21+2*1*2sqrt5)=sqrt(1+20+2*1*2sqrt5)=sqrt(1^2+2*1*2sqrt5+(2sqrt5)^2)=sqrt((1+2sqrt5)^2)=1+2sqrt5`